Topographic Quadrant Analysis of Peripapillary Superficial Microvasculature in Optic Disc Drusen - Yan, Yan; Zhou, Xiao; Chu, Zhongdi; Stell, Laurel; Shariati, Mohammad Ali; Wang, Ruikang K.; Liao, Yaping Joyce (Frontiers in Neurology, 2021)
Background: Limited information is known about the topographic effect of optic disc drusen (ODD) on peripapillary retinal nerve fibers and microvasculature. Objective: To understand the structural and functional impact of ODD in different quadrants of the optic disc. Methods: We performed a retrospective case-control study of 22 ODD patients (34 eyes) and 26 controls (33 eyes) to compare optical coherence tomography (OCT) retinal nerve fiber layer (RNFL), OCT angiography (OCTA), and corresponding static perimetry mean deviation (MD) calculated using the modified Garway-Heath map in different quadrants of the optic disc. OCTA was analyzed using custom MATLAB script to measure 6 parameters in a peripapillary annulus with large vessel removal: vessel area density (VAD), vessel skeleton density (VSD), vessel perimeter index (VPI), vessel complexity index (VCI), flux, and vessel diameter index (VDI). Results: Quadrant analysis revealed that OCTA VAD and VCI were significantly decreased in superior, nasal, and inferior but not temporal quadrant. RNFL, VSD, and VPI were significantly impacted only in the superior and nasal quadrants. Corresponding visual field MDs in all ODD eyes were not different in the 4 quadrants, although eyes with MD equal or worse than – 5dB (32%) had worst visual field corresponding to the superior quadrant of the optic disc (inferior arcuate visual field). Structure-structure comparison of OCT and OCTA showed high correlation of RNFL with multiple OCTA measurements in the superior, nasal, and inferior quadrants but not temporal quadrant. Structure-function analysis revealed significant correlation of VAD and VCI and visual field MD in every quadrant, but RNFL was only significantly correlated in the superior and inferior quadrants. Conclusions: Peripapillary VAD and VCI are decreased in more quadrants than RNFL, supporting the clinical utility of performing OCTA in addition to OCT. Consistent with the most common locations of ODD, 5 OCT/OCTA measurements (VAD, VCI, RNFL, VSD, VPI) are decreased in the superior and nasal quadrants. OCT/OCTA measurements were significantly impacted in contrast to the relatively mild effect on corresponding visual field MD, consistent with the idea that a decrease in objective structural and vascular measurements occurs without parallel change in subjective visual function in ODD.